대한민국 군간부를 위한 단축 형식 우울증 선별 설문지 개발 - 최승연; 변기환; 임명남; 박종익 (Singyŏng chŏngsin ŭihak, 2024)
Objectives This study uses the short-form Center for Epidemiological Studies-Depression Scale (CES-D) to screen for depression among Korean career soldiers, aiming to protect mental health and ensure military stability. Methods The study involves 2922 career soldiers who completed online self-report questionnaires assessing suicidality, depression, anxiety, and social support. Diagnosis of major depressive episodes (MDEs) using the Korean version of the Mini International Neuropsychiatric Interview (K-MINI) was confirmed through Pearson correlation analysis of the 20 CES-D items. The top three correlated items form the Depression Screening Questionnaire for Korean Career soldiers (DSQ-KC). Receiver operating characteristic curves and area under the curve (AUC) values were obtained, with the DSQ-KC total score as the explanatory variable and MDEs as the response variable. Independent t-tests were performed to determine whether suicidality, anxiety, and social support differed based on the cut-off scores of the DSQ-KC. Results In the analysis of each CES-D item with an MDE diagnosis, items 4, 6, and 3 were obtained. The AUC value was 0.958. At a cut-off score of 2, sensitivity and specificity were 93.9% and 89.9%, respectively, with positive and negative predictive values of 14.7% and 99.6%, respectively. Conversely, at a cut-off score of 3, sensitivity and specificity were 83.7% and 94.4%, respectively, with positive and negative predictive values of 27.7% and 98.9%, respectively. Associations with suicidality, anxiety, and use of social networks from cut-off scores of 2 or 3 were examined. Conclusion The DSQ-KC, developed with three reliable items, is user-friendly and can be utilized in suicide prevention projects for career soldiers. KCI Citation Count: 0